(untitled) (Journal of the College of Basic Education, 2026)
The Abbasid Caliph Muhammad al-Amin ibn Harun al-Rashid assumed the caliphate in (193 AH / 809 CE)، amidst turbulent political conditions that quickly worsened as a result of the conflict over the succession with his brother Abdullah al-Ma’mun. This conflict constituted the most prominent revolts of his reign، as it turned into a civil war that threatened the unity of the Abbasid state. The outbreak of these revolts is attributed to al-Amin’s violation of his father’s will to remove al-Ma’mun from the line of succession، in addition to the ethnic rivalry between Arab and Persian powers and the weakness of central control over the provinces. Al-Amin’s stance was characterized by reliance on military force and the political exclusion of his opponents، which led to an escalation of the conflict instead of its containment. These revolts contributed to weakening the prestige of the Abbasid Caliphate and paved the way for prominent political transformations during the reign of al-Ma’mun.